The Global Influenza Hospital Surveillance Network: A Multicountry Public Health Collaboration - Nunes, Marta C; Chauvel, Cecile; Raboni, Sonia M; López-Labrador, F Xavier; Andrew, Melissa K; Badar, Nazish; Baillie, Vicky; Bal, Antonin; Baral, Kedar; Baumeister, Elsa; Boutros, Celina; Burtseva, Elena; et al. (Influenza and other respiratory viruses, 2025)
Respiratory viruses represent a significant public health threat. There is the need for robust and coordinated surveillance to guide global health responses. Established in 2012, the Global Influenza Hospital Surveillance Network (GIHSN) addresses this need by collecting clinical and virological data on persons with acute respiratory illnesses across a network of hospitals worldwide. GIHSN utilizes a standardized patient enrolment and data collection protocol across its study sites. It leverages pre-existing national infrastructures and expert collaborations to facilitate comprehensive data collection. This includes demographic, clinical, epidemiological, and virologic data, and whole genome sequencing (WGS) for a subset of viruses. Sequencing data are shared in the Global Initiative on Sharing All Influenza Data (GISAID). GIHSN uses financing and governance approaches centered around public-private partnerships. Over time, GIHSN has included more than 100 hospitals across 27 countries and enrolled more than 168,000 hospitalized patients, identifying 27,562 cases of influenza and 44,629 of other respiratory viruses. GIHSN has expanded beyond influenza to include other respiratory viruses, particularly since the COVID-19 pandemic. In November 2023, GIHSN strengthened its global impact through a memorandum of understanding with the World Health Organization, aimed at enhancing collaborative efforts and data sharing for improved health responses. GIHSN exemplifies the value of integrating scientific research with public health initiatives through global collaboration and public-private partnerships governance. Future efforts should enhance the scalability of such models and ensure their sustainability through continued public and private support.
Keywords: nemocnice; sekvenování celého genomu; COVID-19; epidemiologické monitorování; Public Health; chřipka lidská; Global Health; Humans; celosvětové zdraví; Hospitals; veřejné zdravotnictví; Whole Genome Sequencing; lidé; Epidemiological Monitoring; Influenza, Human